Análise fitoquímicas e avaliação da atividade e do mecanismo de ação antiúlcera do extrato hidroetanólico das folhas de Helicteres sacarolha A. St. – Hil. et al. - Balogun, Sikiru Olaitan (2014)
Helicteres sacarolha Kunth. (Malvaceae) is a plant found in the Amazon region of Brazil and widely used in folk medicine of several countries for the treatment of gastric disorders, inflammation and infections. The aim of this study was to evaluate the acute and chronic toxicity, the preventive activities (gastroprotective) and curative (anti-ulcer) of hydroethanolic extract of Helicteres sacarolha (EHHs) and to elucidate the possible mechanisms involved in these activities. Additionally, phytochemical analyzes were carried out on EHHs. The leaves of Helicteres sacarolha were macerated in 75% hydroethanol (1:3 w / v) to obtain HEHs. Cytotoxicity of EHHs was evaluated in CHO-K1 and RAW 264.7 cells by the method of Alamar blue and acute animal toxicity in Swiss-Webster mice by Hippocratic test. The subchronic toxicity was evaluated in Wistar rats treated for 30 days with fixed doses of HEHs. Secondary metabolites were analyzed and confirmed by thin layer chromatography (TLC), spectrophotometry and high performance liquid chromatography (HPLC). The gastroprotective activity was assessed using gastric ulcer models of acidified ethanol, piroxicam, water restraint stress (acute models) and acetic acid (chronic) in rodents. The anti-Helicobacter pylori potential of HEHs was evaluated by broth microdilution method studies, determining the minimum inhibitory concentration (MIC). Antioxidant studies in vitro (DPPH, FRAP, chelating iron and linoleic acid tests) and in vivo (catalase and myeloperoxidase) were evaluated. The antisecretory activity of HEHs was assessed by the pylorus ligation in rats the likely mechanism of action of HEHs was evaluated ulcerated animals with acidified ethanol and pretreated with yohimbine, glibenclamide, indomethacin and L-NAME. The profile of proinflammatory and anti-inflammatory cytokines was evaluated in acetic acid ulcerated animals. HEHs presented low cytotoxicity in CHO-K1 and RAW 264.7, with IC50> 200 /mL. When administered orally at doses up to 2000 mg / kg in male mice and 4000 mg / kg in female mice, caused no change HEHs in signs and symptoms evaluated. In the subchronic toxicity test no significant changes were observed by treatment with HEHs in the parameters observed, except elevation of leukocytes (28%), basophils (ca.4 times) and decrease of neutrophils (18%), monocytes (65%) , hemoglobin (3.6%) and hematocrit (6.5%) that were not followed by clinical and hsitopatológicas changes. Total phenols and flavonoids were 19.9% and 14.4% respectively. The major compounds detected in HEHs were ellagic acid (6%) and morin (0.3%). HEHs demonstrated antiulcer activitis in the acute and chronic ulcer models. The antiulcer activity of HEHs involved the participation of NO, α-receptor, prostaglandins, K+ - ATP channels and antioxidant mechanisms and is dependent only on inhibition of gastric volume but not the acid secretion mechanisms. The ulcer healing action of HEHs involved attenuation of pro-inflammatory cytokines. HEHs was inactive against Helicobacter pylori. The results of this study confirm the popular use of the leaves of Helicteres sacarolha in gastric ulcers and that HEHs has low toxicity and a multitargeted action. The main metabolic constituents are the phenols and flavonoids, with ellagic acid and morin being the major classes of compounds. Ellagic acid is possibly involved in the gastroprotective antiulcer action of HEHs. Further experiments are required to advance preclinical validation of HEHs with the aim of developing an anti-ulcer phytotherapy.